Faktor - Faktor yang Mempengaruhi Kejadian Stunting pada Balita Usia 24 - 59 Bulan - Siti Ma`wah Doifah,; Andriyani Andriyani,; Nurmalia Lusida, (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Stunting is a failure to achieve physical development measured by weight for age. The limitation of stunting is height according to age based on Z-score equal to or less than -2SD (Standard Deviation) below the standard average. In 2005 - 2011 Indonesia ranked fifth with the highest prevalence of stunting. The purpose this study was to analyze the factors that influence the incidence of stunting in children aged 24-59 months. This study used a literature review method conducted by searching for relevant journals trough Google Scholar, Garuda, PubMed and DOAJ database. Inclusion criteria for reviewing the content of references in English and Indonesia publish in the last ten years. Research result from various literatures show that research finding from various sources indicate that the factor influencing stunting toddler aged 24-59 months include maternal knowledge, exclusive breastfeeding, and disease history.